PEDIATRIC DRUG TRIALS IN CHINA. Issue 1 (14th December 2015) - Hao, Guo-Xiang; Wang, Xiao-Ling; Shen, A-Dong; Jacqz-Aigrain, Evelyne; Zhao, Wei
Abstract : Background and objective: The introduction of the Pediatric Regulation by the European Union, together with the renewal of the Pediatric Rule by the US Food and Drug Administration on the requirements for pediatric labeling made it mandatory for sponsors to develop drugs for the pediatric population and promotes the pediatric drug trials in Europe and US. However, very little is known about the situation of pediatric drug trials in other countries, particularly in China, home to nearly 300 millions children. In order to support the global research in pediatric drug development and clarify the specific characteristics of pediatric drugs trials in China, we analyzed the drug trials registered in the Chinese Clincial Trial Registry database. Methods: The pediatric drug trials registered in Chinese Clincial Trial Registry database between 2007 and 2014 were analyzed. The following information was extracted from the database by two authors: type of the trial, registered time, drug name, inclusion and exclusion criteria, population, number of patients, and sponsor. Results: Among all (4786) trials registered, 729 trials (15.2%) involved the pediatric population, and only 308 trials (6.4%) were pediatric drug trials. From 2007 to 2013 pediatric drug trials increased from 3 to 121. There were 66 pediatric drug trials including Chinese traditional medicine. Conclusion: Our results demonstrated for the first time the situation of pediatric drug trials in China. Consistent with the initiatives of promoting pediatric drug development in Europe and US, the pediatric drug trial in China made a significant progress after 2012. The pediatric drug legislation is urgently needed in China.